ANOMIE AND CRIME IN THE FAMILY IN A TRADITIONAL AND TRANSITIONAL SOCIETY - Rira, Miranda (European Scientific Journal, ESJ, 2012)
This paper aims at elaborating and understanding of murder and homicide in the Albanian family. During the last two decades, Albanians have experienced rapid changes, great turmoil and transitions from a communist, traditional ethnic-based society towards a new era of modern norms of a â€œwesternâ€ society. We will build on Durkhemianâ€™s paradigm on anomie as the first leading cause to crime and deviance. We hypothesize that: â€œwhen ethnic-based family oriented societies face new rules and regulations, a deregulation of the social system and a disruption of family ties is displayed, hence a domain of anomie is created, a threat of collective conscience of the society, a state of being lost between past and future which influences people to be more prone to committing murder and crimes towards society, towards their families and towards themselves, committing suicide. The second hypotheses is that: the honor killings are nothing but a rudiment of the old patriarchal societies and an expression of the collision between the new imposed norms and old, well-established traditions.